The Role of Economics in the Fight Against Climate Change - McClain, Tom (Kansas State University. K-State Libraries, 2021)
Over the past century, humans have drained our planet’s natural resources and altered its climate through increasing carbon emissions. Efforts to protect the environment and mitigate warming have yielded little progress. This project seeks to provide a starting point for policymakers, academics, and voters alike by applying economic research and principles to climate change. An analysis of the issue reveals that markets fail to incentivize businesses to consider the long-term health of the planet when making decisions. If market deficiencies are to blame for the conditions that cause pollution and global warming, then economics has powerful potential to direct firms toward more environmentally responsible behaviors. With this foundation in mind, the paper identifies three criteria that can be used to evaluate policy instruments that seek to address climate change. First, policies must force firms to account for the environmental cost of their emissions. Second, policies must incentivize the innovation of more sustainable business practices. Finally, policies should not be so complex or heavy-handed that it is impossible to raise the political support needed to enact them. These criteria are applied to four major policy tools: command and control approaches, information disclosure programs, emissions trading systems, and pollution taxes. In each case, this paper reviews the economic debate on the policy option and examines the varying degrees of scope and success achieved by these policies when implemented. Carbon taxes are identified as a particularly promising candidate for reducing emissions on a large scale. The project concludes by emphasizing that well-designed policy action by wealthy nations, especially the U.S., is critical to stopping climate change and protecting the planet.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, grand prize
Keywords: Climate Change; Sustainable Business Practices; Emissions Trading Systems; Environmental Economics; Carbon Tax; Information Disclosure Program